Analysis of the Role of Standard Costs in Increasing Production Cost Efficiency: A Case Study of PT. XYZ - Musfitria, Anessa; Iswandi, Mei; Djamaa, Wahjuny; Bakti, Rizal; Eldianson, Rio (LPPM Institut Bisnis dan Informatika Kesatuan, 2023)
This study aims to determine the role of standard costs in increasing the efficiency of production cost control at PT.XYZ. The study investigates the effectiveness of standard costs in enhancing the efficiency of production cost control, with a focus on determining standard costs for raw materials in the year 2021. The data analysis technique used in this study is descriptive quantitative. Based on the results, it can be concluded that standard costs play a significant role in improving the effectiveness of efficient production cost control. The existence of standard costs facilitates companies in determining buying and selling prices for materials. Despite facing unfavorable differences in labor costs, especially in the aggregate processing department's salaries, the application of standard costs resulted in significant cost efficiency in raw material expenses. The overall profitability of the enterprise remained favorable, with the margin between profitable and unprofitable costs supporting the strategic advantage of employing standard costs as a control mechanism. The findings contribute to the theoretical understanding of the practical utility of standard costs in the context of production cost management. This research provides valuable insights for both researchers and practitioners, emphasizing the importance of incorporating standard cost methodologies into managerial decision-making processes to enhance cost control strategies within organizations.